Genetic tolerance to low temperatures in irrigated rice (Revista Ciência Agronômica, 2020)
The aim of this study was to characterise genetic variability to low-temperature tolerance in the emergence stageof irrigated-rice genotypes under controlled and field conditions. Thirty-seven genotypes were evaluated, interspersed withcontrols of different levels of low-temperature tolerance. The design used was of randomised blocks with three replications.The genotypes were submitted to germination and emergence in controlled-temperature trials at 13 oC (Trial I) and 17 oC (TrialII), and in field environments with no cover (Trial III) and with a cover of polyethylene (Trial IV), where the soil temperaturewas monitored. The evaluations were carried out daily by counting the emerged seedlings and later inferring the speed ofemergence index (SEI). The results showed (experiment I to IV) that the SEI varied from 0.61 to 4.23, increasing by 0.4259for each 1 oC increase in soil temperature. The genotypes Ostiglia, Diamante, Baldo, Carnaroli, Selenio, Loto e Amarelo, ofsubspecies japonica, and Ringo Miara-AC and Arelate, of subspecies indica, are promising sources of genetic tolerance to lowtemperature. Temperatures of less than 17 ºC reduce the number of emerged seedlings and delay development in each of therice genotypes under test, with a greater or lesser negative effect on the initial plant stand per unit area.